Designing Project-Based Learning in research proposal writing: Its effect, problems, and scaffolding utilized - Ni Nyoman Padmadewi; Luh Putu Artini; Ni Made Ratminingsih; I Putu Andre Suhardiana; Ahmad Zamzam; Putu Adi Krisna Juniarta (Universitas Syiah Kuala, 2023)
Project Based Learning (PBL) is highly important to be suited to the student’s needs as a guide in writing research proposals. The objectives of the study were to (1) describe the PBL design based on the students’ needs, (2) identify the problems encountered during the project writing, (3) describe the scaffolding utilized, and (4) analyze the effect of PBL implementation on the quality of students’ research proposal. The research used mixed methods in the form of a research and development design using the ADDIE model (which consists of steps of analyzing needs, designing the product of PBL, developing, and implementing it, and conducting evaluation). The participants were 20 respondents during the needs analysis, two lecturers, and three intact classes of 69 students during PBL implementation. Data were collected through questionnaires, interviews, a document study, and an experiment. A needs analysis was conducted using the Organizational Element Model (OEM), from which the PBL was developed. The data were analyzed using qualitative and quantitative analyses. The findings revealed that the PBL designed based on students’ needs has characteristics such as it is in the form of a framework and has systematic stages of teaching, being technology friendly, and being supported with various scaffoldings. The problems encountered concerned both grammar and content. The implementation of the PBL framework was found to have a significant effect on students’ research proposal writing in Research Method Course and develop their independence and learning autonomy.